Synthesis and structural characterization of copper–cuprizone complexes. Issue 27 (29th June 2022) - Pushie, M. Jake; Summers, Kelly L.; Nienaber, Kurt H.; Pickering, Ingrid J.; George, Graham N.
Abstract : The chemistry of copper with cuprizone has challenged chemists for over 70 years. We characterize the classical 'blue' product, containing Cu(iii ) and hydrolyzed cuprizone, and a green multimeric Cu(ii ) product, containing unhydrolyzed cuprizone. Abstract : Copper(ii ) coordination by bis(cyclohexanone)oxalyldihydrazone (also known as cuprizone), resulting in the formation of an intensely coloured blue complex, was first reported over 70 years ago. The cuprizone reaction has been employed in colourimetric tests for the presence of trace levels of copper. Cuprizone administration in C57BL/6 mice also leads to demyelination over time – a consequence that appears to be due to copper dyshomeostasis – and this has led to use of cuprizone as the leading method for toxicant-induced generation of an animal model of demyelination since its first use in the 1960s. Despite broad interest in cuprizone and its ability to bind copper there have been relatively few studies to structurally characterize the copper coordination properties of this ligand. In the absence of an aqueous medium, such as neat alcohol, copper and cuprizone exclusively form an amorphous green precipitate. Under aqueous conditions, where a large excess of cuprizone (relative to copper) is present, the blue complex that is synonymous with copper–cuprizone coordination is predominantly formed. The blue and green copper–cuprizone products demonstrate poor solubility and present challenges for conventional structure characterization methods, such as X-ray crystallography or nuclear magnetic resonance spectroscopy. By combining mass spectrometry, X-ray absorption spectroscopy, computational chemistry, and other techniques, a self-consistent picture of the copper coordination structures of the blue and green complexes is revealed – confirming that the blue complex is in the Cu(iii ) state, containing two hydrolyzed cuprizone ligands per metal centre, while the green complex represents an extended oligomeric complex, comprised of repeating Cu(ii ) centres that lie 4.8 Å apart and are bridged by unhydrolyzed cuprizone donors.